The Influence of Tax Service Quality, Tax Sanctions, Taxpayer Awareness, and Tax Socialization on Individual Taxpayer Compliance - Astuti, Rheynisa Dwi; Astuti, Tutut Dewi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2022)
This research aims to find out how the quality of tax services, tax sanctions, taxpayer awareness, and tax socialization influence individual taxpayer compliance. This research involves individual taxpayers who have NPWPs in the Sleman Regency, Yogyakarta. This research uses an easy-to-use sampling method, and data is collected by distributing questionnaires with a 1-5 Likert scale via Google Forms. This research used 100 respondents as samples. Validity testing, classical assumptions, multiple linear regression, and hypotheses are the research methods used in this research. Studies show that individual taxpayer compliance is not influenced by the quality of tax services; tax sanctions have a positive influence on individual taxpayer compliance; Taxpayer awareness has a positive influence on individual taxpayer compliance; and taxpayer socialization does not influence individual taxpayer compliance.